Endothelin B Receptors on Primary Chicken Müller Cells and the Human MIO-M1 Müller Cell Line Activate ERK Signaling via Transactivation of Epidermal Growth Factor Receptors. - Mohammad Harun-Or-Rashid; Dardan Konjusha; Caridad Galindo-Romero; Finn Hallböök (PLoS ONE, 2016)
Injury to the eye or retina triggers Müller cells, the major glia cell of the retina, to dedifferentiate and proliferate. In some species they attain retinal progenitor properties and have the capacity to generate new neurons. The epidermal growth factor receptor (EGFR) system and extracellular signal-regulated kinase (ERK) signaling are key regulators of these processes in Müller cells. The extracellular signals that modulate and control these processes are not fully understood. In this work we studied whether endothelin receptor signaling can activate EGFR and ERK signaling in Müller cells. Endothelin expression is robustly upregulated at retinal injury and endothelin receptors have been shown to transactivate EGFRs in other cell types. We analyzed the endothelin signaling system in chicken retina and cultured primary chicken Müller cells as well as the human Müller cell line MIO-M1. The Müller cells were stimulated with receptor agonists and treated with specific blockers to key enzymes in the signaling pathway or with siRNAs. We focused on endothelin receptor mediated transactivation of EGFRs by using western blot analysis, quantitative reverse transcriptase PCR and immunocytochemistry. The results showed that chicken Müller cells and the human Müller cell line MIO-M1 express endothelin receptor B. Stimulation by the endothelin receptor B agonist IRL1620 triggered phosphorylation of ERK1/2 and autophosphorylation of (Y1173) EGFR. The effects could be blocked by Src-kinase inhibitors (PP1, PP2), EGFR-inhibitor (AG1478), EGFR-siRNA and by inhibitors to extracellular matrix metalloproteinases (GM6001), consistent with a Src-kinase mediated endothelin receptor response that engage ligand-dependent and ligand-independent EGFR activation. Our data suggest a mechanism for how injury-induced endothelins, produced in the retina, may modulate the Müller cell responses by Src-mediated transactivation of EGFRs. The data give support to a view in which endothelins among several other functions, serve as an injury-signal that regulate the gliotic response of Müller cells.